THE INTERACTIVE ROLE OF ETHICAL MANAGEMENT IN STRENGTHENING THE RELATIONSHIP BETWEEN PROFESSIONAL VALUES AND ORGANIZATIONAL BRILLIANCE - Lecturer. Dr. Jasim Saad Jasim (Scholars Digest Publishing, 2024)
The main research problem lies in the importance of studying the reality of ethical management of the Departments of the faculties of the University of Dhi Qar and its impact on the achievement and consolidation of professional values in order to improve its position in society, increase its competitiveness, distinguish its results by quality, and increase the degrees of loyalty and affiliation among its employees in order to raise their performance level. The aim of this research is to discover the interactive impact of ethical management on the relationship between professional values and organizational brilliance among the faculty members of the studied faculties and measure the levels of the studied variables. The research was conducted on a deliberate sample composed of faculty members from some faculties of the University of Dhi Qar, where (235) questionnaires designed by the researcher were distributed, and after analyzing the results, it turned out that the results of the respondents were high in terms of ethical management, as the faculty members have a high awareness of the extent to which the Departments of the, Not to mention the relationship between professional values and the organizational brilliance of faculty members, one of the most important recommendations is the emphasis by the college departments on practicing ethical behaviors and upright practices because of their great impact in promoting professional values and thinking about the quality requirements for organizational performance.
Keywords: Ethical management, Professional values, Organization, brilliance, Strengthening, Colleges.